Asymmetric Syntheses of Polycyclic Amines - Houlsby, I (2017)
This thesis centers on the asymmetric synthesis of polycyclic amines, focussing on three distinct classes of polycyclic alkaloid natural products. The work aims to use common methodology of lithium amide conjugate additions as the source of asymmetry in all cases, and for each product class a single strategy is used to synthesise a variety compounds. Chapter 1 describes the importance of the synthesis of polycyclic alkaloids, highlighting three classes of compounds and documenting prior synthetic strategies. The classes discussed are: the Hancock alkaloids, hydroxymethyl-substituted azabicycles, and the tetraponerine alkaloids. Chapter 2 describes two separate synthetic strategies towards the Hancock alkaloid (–)-cuspareine, one using a benzyne mediated cyclisation and one a Buchwald-Hartwig cyclisation. The Buchwald-Hartwig methodology was also applied in the synthesis of two more Hancock alkaloids (–)-galipinine and (–)-galipeine; the synthesis of (–)-galipeine led to a reassignment of the structure of the natural product. Chapter 3 describes work in the synthesis of four [x.y.0]-azabicycles with differing in ring sizes (x, y = 3, 4). The strategy employs sequential SN2-like ring-closing reactions to form the bicyclic structures where pyrrolizidine, indolizidine and quinolizidine scaffolds can be accessed. Amongst the products are two natural alkaloids, (–)-lupinine and (+)-isoretronecanol. Chapter 4 describes the synthesis of all eight tetraponerine alkaloids T1–8. Two sequential lithium amide conjugate addition reactions allow for the synthesis of the differing ring-sizes and diastereoisomers displayed by the eight alkaloids. Ring-closing metathesis and diamine condensation with 4-bromobutanal provide the ring-closing steps in the syntheses. Chapter 5 contains full experimental procedures and characterisation data for all compounds synthesised in Chapters 2–4.